2022
DOI: 10.3390/medicina58121843
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pre-Existing Long-Term β-Blocker Therapy and the Outcomes of Sepsis-Associated Coagulopathy: A Retrospective Study

Abstract: Background and Objectives: Previous studies have suggested that long-term β-blocker therapy before sepsis is associated with reduced mortality. Sepsis-associated coagulopathy (SAC) remains a common complication in patients with sepsis and is associated with increased mortality. Adrenergic pathways are involved in the regulation of the coagulation system. Pre-existing long-term β-blocker therapy may have potentially beneficial effects on SAC and has yet to be well characterized. We aimed to assess the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Of them, nine studies in total were excluded since they reported data on other antihypertensive drugs and an additional number of ten studies were excluded because they assessed the effect of ongoing or newly prescribed beta-blockers on patients with sepsis. Finally, a total of 17 studies (16)(17)(18)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), comparing premorbid beta-blocker use with controls in patients with sepsis, were selected for the analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of them, nine studies in total were excluded since they reported data on other antihypertensive drugs and an additional number of ten studies were excluded because they assessed the effect of ongoing or newly prescribed beta-blockers on patients with sepsis. Finally, a total of 17 studies (16)(17)(18)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), comparing premorbid beta-blocker use with controls in patients with sepsis, were selected for the analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%